Green chemistry appended synthesis, metabolic stability and pharmacokinetic assessment of medicinally important chromene dihydropyrimidinones. Issue 24 (15th December 2019) - Dash, Ashutosh K.; Mukherjee, Debaraj; Dhulap, Abhijeet; Haider, Saqlain; Kumar, Deepak
Graphical abstract: Abstract: A green chemistry approach has been developed for the synthesis of chromene dihydropyrimidinone (CDHPM) using recyclable Fe/Al pillared clay catalyst. Pharmacokinetic parameters like aqueous solubility, lipophilicity, P-glycoprotein (P-gp) ATPase activity, permeability, plasma protein binding, red blood cell (RBC) partitioning, metabolic stability in liver microsomes and in silico computations have been studied for the most potent anticancer chromene dihydropyrimidinone hybrid 1 . This compound exhibited low solubility, optimum lipophilicity, no P-gp inhibitory activity, intermediate permeability, high plasma protein binding, low RBC partitioning, acceptable metabolic stability in rat liver microsomes (RLM) as well as human liver microsomes (HLM) with transitional hepatic extraction ratio.